R‐spondin 1 and noggin facilitate expansion of resident stem cells from non‐damaged gallbladders. (18th March 2016) - Lugli, Natalia; Kamileri, Irene; Keogh, Adrian; Malinka, Thomas; Sarris, Michalis E; Talianidis, Iannis; Schaad, Olivier; Candinas, Daniel; Stroka, Deborah; Halazonetis, Thanos D
Abstract: Pioneering studies within the last few years have allowed the in vitro expansion of tissue‐specific adult stem cells from a variety of endoderm‐derived organs, including the stomach, small intestine, and colon. Expansion of these cells requires activation of the receptor Lgr5 by its ligand R‐spondin 1 and is likely facilitated by the fact that in healthy adults the stem cells in these organs are highly proliferative. In many other adult organs, such as the liver, proliferating cells are normally not abundant in adulthood. However, upon injury, the liver has a strong regenerative potential that is accompanied by the emergence of Lgr5‐positive stem cells; these cells can be isolated and expanded in vitro as organoids. In an effort to isolate stem cells from non‐regenerating mouse livers, we discovered that healthy gallbladders are a rich source of stem/progenitor cells that can be propagated in culture as organoids for more than a year. Growth of these organoids was stimulated by R‐spondin 1 and noggin, whereas in the absence of these growth factors, the organoids differentiated partially toward the hepatocyte fate. When transplanted under the liver capsule, gallbladder‐derived organoids maintained their architecture for 2 weeks. Furthermore, single cells prepared from dissociated organoids and injected into the mesenteric vein populated the liver parenchyma of carbon tetrachloride‐treated mice. Human gallbladders were also a source of organoid‐forming stem cells. Thus, under specific growth conditions, stem cells can be isolated from healthy gallbladders, expanded almost indefinitely in vitro, and induced to differentiate toward the hepatocyte lineage. Synopsis: Stem/progenitor cells isolated from healthy gallbladders can be expanded for more than one year as organoids in vitro in the presence of R‐spondin 1 and noggin. These cells can be induced to differentiate toward the hepatocyte fate and can be transplanted in mouse livers. Gallbladder epithelial cells express markers of both biliary duct cells and hepatocytes and can be propagated in tissue culture as organoids for more than a year. Growth of gallbladder‐derived organoids is stimulated by R‐spondin 1 and noggin, whereas removal of these two growth factors leads to partial differentiation toward the hepatocyte fate. Human gallbladders are also an expandable source of organoid‐forming stem/progenitor cells. Abstract : Stem/progenitor cells isolated from healthy gallbladders can be expanded for more than one year as organoids in vitro in the presence of R‐spondin 1 and noggin. These cells can be induced to differentiate toward the hepatocyte fate and can be transplanted in mouse livers.